AN ANALYSIS OF STUDENTS’ ERROR IN WRITING SIMPLE SENTENCES - Budi Nugraha Hidayat; Maryani Maryani (IKIP Siliwangi, 2020)
Language is needed whether it is written or spoken. Language is very necessary for people as a mean of communication. The objective of this research was to analyze the students’ ability in writing simple sentences in past tense. This research used qualitaive research and the data were analyzed to investigate the second year of students’ ability in writing English simple sentences. The participant of this research was consisted of 32 students. Data analysis shows that 27.81% the students have difficulties in structure English simple sentence in past tense. Furthermore 38.12% the students have difficulties using regular verbs in past tense, whereas 71.8% the students have difficulties using irregural verbs in past tense. Over all, the students’ ability in writing English simple sentence in past tense can be considered in medium level. This is due to their confusion in using verb (regular verbs and irregular verbs).